Magnetic Hyperthermia in the 400–1,100 kHz Frequency Range Using MIONs of Condensed Colloidal Nanocrystal Clusters - Kouzoudis, Dimitris; Samourgkanidis, Georgios; Kolokithas-Ntoukas, Argiris; Zoppellaro, Giorgio; Spiliotopoulos, Konstantinos (Frontiers in Materials, 2021)
In the current work, the hypothesis that the hyperthermia power of magnetic nanoparticles is proportional to the frequency of the applied AC, is tested. To examine the validity of this hypothesis, an AC magnetic field of 3mT amplitude was produced over a range of 400 kHz to 1.1 MHz and applied to a dilute aqueous ferrofluid solution composed of ferrous magnetic nanoparticles. It is a common belief in the literature that the hyperthermia power is an increasing function of frequency but there were not anywhere a systematic study prior to our work to prove this hypothesis. In the current work such a systematic study takes place and indeed it reveals a direct relationship between the two physical quantities. In particular, the SAR parameter which is the ratio of the heat power in Watts produced per nanoparticle mass in grams, is linear to a good degree to the frequency with a step of roughly 30 W/g per a 100 kHz increase. Our SAR values were in the 100 to 300 W/g range which is within the range of values reported elsewhere. Additionally, our measured data of temperature versus time at each frequency, were explained in terms of simple thermodynamic arguments, in order to extract useful thermodynamic parameters for the magnetic nanoparticles, in particular the heat power that they produce.